1997
DOI: 10.1042/bj3230371
|View full text |Cite
|
Sign up to set email alerts
|

Activation of cGMP-stimulated phosphodiesterase by nitroprusside limits cAMP accumulation in human platelets: effects on platelet aggregation

Abstract: cGMP enhances cAMP accumulation in platelets via cGMP-inhibited phosphodiesterase (PDE3) [Maurice and Haslam (1990) Mol. Pharmacol. 37, 671-681]. However, cGMP might also limit cAMP accumulation by activating cGMP-stimulated phosphodiesterase (PDE2). We therefore evaluated the role of PDE2 in human platelets by using erythro-9-(2-hydroxy-3-nonyl)adenine (EHNA) to inhibit this enzyme selectively. IC50 values for the inhibition of platelet PDE2 by EHNA, with 10 microM cAMP as substrate in the absence and in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 25 publications
4
62
0
1
Order By: Relevance
“…In platelets or adrenal glomerulosa cells, increased cGMP levels resulting from NO or ANP, activated PDE2, and reduced cAMP. [27][28][29][30] In line with this, previous studies have shown that increased cAMP levels blocked superoxide formation in neutrophils 31 and that the nonhydrolyzable S(p)-cAMPS decreased the levels of activated Rac1 by inhibition of the Rac1-specific guanine nucleotide exchange factor p-Rex1. 32 However, inhibition of other cAMP-hydrolyzing PDEs, namely PDE3 or PDE4, decreased ROS generation in isolated rat glomeruli 33 or in mesangial cells.…”
Section: Pde2 Stimulates Formation Of Ros Via Rac1 and Nox2supporting
confidence: 59%
“…In platelets or adrenal glomerulosa cells, increased cGMP levels resulting from NO or ANP, activated PDE2, and reduced cAMP. [27][28][29][30] In line with this, previous studies have shown that increased cAMP levels blocked superoxide formation in neutrophils 31 and that the nonhydrolyzable S(p)-cAMPS decreased the levels of activated Rac1 by inhibition of the Rac1-specific guanine nucleotide exchange factor p-Rex1. 32 However, inhibition of other cAMP-hydrolyzing PDEs, namely PDE3 or PDE4, decreased ROS generation in isolated rat glomeruli 33 or in mesangial cells.…”
Section: Pde2 Stimulates Formation Of Ros Via Rac1 and Nox2supporting
confidence: 59%
“…PDE2 enzymes hydrolyze either cAMP or cGMP; hydrolysis is stimulated by cGMP binding to amino terminal allosteric regulatory sites known as GAF domains (Martinez et al, 2002). A role for PDE2 in regulating cGMPmediated effects in blood platelets (Dickinson et al, 1997), cardiomyocyte and VEC (Mery et al, 1995), and adrenal granulosa cells (Juilfs et al, 1997) have each been reported. Indeed, natriuretic peptides or organic nitrates/nitric oxide donors elevate cellular cGMP and activate PDE2 in some of these cells (Mery et al, 1995;Dickinson et al, 1997).…”
Section: Pde2mentioning
confidence: 99%
“…This cross-talk between the cGMP and cAMP pathways probably occurs in other cellular settings as well. For example, in platelets it is thought that high levels of NO elicit high cGMP accumulation that activates PDE2 and reduces cAMP (Dickinson et al, 1997;Dunkern and Hatzelmann, 2005). However, at lower cGMP levels PDE2 inhibitors alone have little effect on platelet aggregation in comparison to PDE3 inhibitors as PDE3 seems to play a more prominent role in cAMP regulation under these conditions.…”
mentioning
confidence: 99%